"How I Wish This Thing Was Initiated 100 Years Ago!" Willingness to Take Daily Oral Pre-Exposure Prophylaxis among Men Who Have Sex with Men in Kenya. - Robinson Njoroge Karuga; Serah Nduta Njenga; Rueben Mulwa; Nduku Kilonzo; Prince Bahati; Kevin O'reilley; Lawrence Gelmon; Stephen Mbaabu; Charles Wachihi; George Githuka; Michael Kiragu (PLoS ONE)
Background The MSM population in Kenya contributes to 15% of HIV incidence. This calls for innovative HIV prevention interventions. Pre-exposure prophylaxis (PrEP) has been efficacious in preventing HIV among MSM in trials. There is limited data on the willingness to take daily oral PrEP in sub-Sahara Africa. PrEP has not been approved for routine use in most countries globally. This study aimed to document the willingness to take PrEP and barriers to uptake and adherence to PrEP in Kenya. The findings will inform the design of a PrEP delivery program as part of the routine HIV combination prevention. Methods Eighty MSM were recruited in 2 Counties in December 2013. Quantitative data on sexual behaviour and willingness to take PrEP were collected using semi-structured interviews and analysed using SPSS. Qualitative data on knowledge of PrEP, motivators and barriers to uptake and adherence to PrEP were collected using in-depth interviews and FGDs and analysed using Nvivo. Analysis of data in willingness to take PrEP was conducted on the HIV negative participants (n = 55). Results 83% of MSM were willing to take daily oral HIV PrEP. Willingness to take PrEP was higher among the bi-sexual and younger men. Motivators for taking PrEP were the need to stay HIV negative and to protect their partners. History of poor medication adherence, fear of side effects and HIV stigma were identified as potential barriers to adherence. Participants were willing to buy PrEP at a subsidized price. Conclusions There is willingness to take PrEP among MSM in Kenya and there is need to invest in targeted education and messaging on PrEP to enhance adherence, proper use and reduce stigma in the general population and among policy makers.